Abnormal Psychology - Butcher, James N., 1933- ; Mineka, Susan M. and Hooley, Jill M. (Chennai, India Pearson Education, 2016)
Revision of: Abnormal psychology / James N. Butcher, University of Minnesota, Susan Mineka, Northwestern University, Jill M. Hooley, Harvard University. Sixteenth edition
Include Index
Keywords: Psychology, Pathological -- Psychology